Postoperative Complications of Surgical Positioning in the Elderly Orthopaedic Patient - Leonard, Regina (Operating Room Nurses Association of Canada Journal, 1993)
This paper addresses the elderly population from the perspective of physiological and anatomical changes which occur throughout the aging process. Recommendations to enhance elderly patient wellbeing throughout the perioperative experience are given including achieving integrity of the body systems, positions used for surgery, and actual and potential problems which may occur as a result of prolonged positions.